Avaliação do nível de satisfação dos clientes de tratores agrícolas - Martins, Diego Fank (2006)
This work has as objective to diagnose the satisfaction level of users with the agricultural tractors, considering their brands and the satisfaction level of the agricultural tractor enterprise clients in Santa Maria region and nearby cities. Another objectives were to classify the sampled tractors in relation to the potency; to identify the main problems of the tractors, reporting the main sampled brands; to obtain technical and economical information in the enterprises about the maintenance frequency of tractors. The research was carried out through a questionnaire application to the agricultural tractor owners of 14 Central Depression cities, including 125 rural properties. Another part of the research presents the information about the tractor maintenance which was developed at agricultural tractor enterprises in Santa Maria. In the end of this work, it was concluded that John Deere and Massey Ferguson brands present some advantage in relation to the satisfaction of clients, independently of the tractor potency category . When considered the level of tractor potency, John Deere and Massey Ferguson brands presented, again, some advantages in relation to the others from the II potency category. However, John Deere presented the highest satisfaction level of the clients concerning the III potency category. Related to the enterprise satisfaction, John Deere (Verdes Valles) has the best levels of satisfaction. Related to the tractor classification concerning the machine potency, there was a tendency to II potency category tractors, except John Deere which has got bigger tractors. From the four categories adopted by ANFAVEA (2005), 59,7 % of tractors are in the II potency category. Due to the question of significance, in this work, it was considered only I and II potency categories. Among the most frequent problems found in the research, the highest occurrences are related to the ADT ( auxiliary frontal traction), mainly in the tractors which work in flooded soil (irrigated rice), since the water and mud seeping bring damages to the system. Even though it was one of the objectives, it was impossible to compare the price information of services and tools from the enterprises due to the technical differences in the maintenance and constitution plan of each tractor brand as well as the difficulty in obtaining information from all enterprises.